Enfances pieds-noirs, enfances juives, enfances pataouètes (Notes sur l’enfance algérienne comme paradis perdu) - Costantini, Alessandro (Ponti/Ponts, 2021)
This article deals with Francophone literatures from a very peculiar point of view. It deals with an image of Maghreb that is now rejected and banished for its colonial nature as well as its nostalgia for colonization and its times. The texts that will be here analyzed are mostly memoirs and novels depicting the authors’ childhood. In general, they relate the more or less traumatic memories of a childhood / adolescence presented as a paradise long lost. The trauma derived from losing their land – the exodus from an Algeria by which they feel rejected – results in the characters’ identity crisis. Though the sense of loss the characters experience is almost the same, each narrative presents their individual struggles to try to find a way to process it.